Follow the money: Does the financial sector intermediate natural resource windfalls?. (February 2023) - Beck, Thorsten; Poelhekke, Steven
Highlights: Why is the financial sector underdeveloped in resource-rich economies? Slower growth in financial deposits and lending after a natural resource windfall. Effect is driven by countries with repressed financial systems and weak governance. And a stronger role of government in channelling financial capital into the economy. Lack of private financial intermediation of natural resource windfalls. Hampers the development of the financial sector. Abstract: Why is the financial sector underdeveloped in resource-rich economies? Using a large panel dataset, we find slower growth in both financial sector deposits and private sector lending in countries that experience an unexpected natural resource windfall as measured by shocks to exogenous world prices. This effect is driven by countries with repressed financial systems and weak governance structures. The smaller role for the financial sector is accompanied by a stronger role of governments in channeling financial capital into the economy. The lack of private financial intermediation of natural resource windfalls hampers the development of the financial sector, which we interpret as evidence for a resource curse in financial development.